2019
DOI: 10.1177/0895904819886323
|View full text |Cite
|
Sign up to set email alerts
|

The Development and Dynamics of Public–Private Partnerships in the Philippines’ Education: A Counterintuitive Case of School Choice, Competition, and Privatization

Abstract: Educational public–private partnerships (EPPP) have been widely implemented in the Philippines, primarily through the Education Service Contracting (ESC) voucher. Yet, the effects of this voucher on privatization of education, school choice, and competition dynamics remain largely understudied. This article addresses this gap through an investigation of families’ school choice patterns and schools’ logics of action in the Philippines’ education. Paradoxically, despite the pro-private sector impetus of the Phil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 26 publications
0
15
0
Order By: Relevance
“…The authors’ findings show how families in low-income settings are constrained by unequal distributions of school choice subsidies and how their choices are contingent on social networks, educational background, geography, and social selectivity (Moschetti & Verger, this issue). The final paper in this section, by Andreu Termes, D. Brent Edwards, Jr., and Antoni Verger, describes how educational public–private partnerships (EPPPs) have been implemented in the Philippines through a voucher system, leading to increasing levels of school stratification and segregation (Termes, Edwards, & Verger, this issue). The authors employ a conceptual framework that focuses on schools’ logics of action and families’ patterns of choice in the “lived” spaces of competition—the socially and geographically bound spaces of reciprocally oriented interactions between schools and families that operate as “fields” (Woods, Bagley, & Glatter, 1998).…”
Section: Overview Of the Yearbook’s Contributionsmentioning
confidence: 99%
“…The authors’ findings show how families in low-income settings are constrained by unequal distributions of school choice subsidies and how their choices are contingent on social networks, educational background, geography, and social selectivity (Moschetti & Verger, this issue). The final paper in this section, by Andreu Termes, D. Brent Edwards, Jr., and Antoni Verger, describes how educational public–private partnerships (EPPPs) have been implemented in the Philippines through a voucher system, leading to increasing levels of school stratification and segregation (Termes, Edwards, & Verger, this issue). The authors employ a conceptual framework that focuses on schools’ logics of action and families’ patterns of choice in the “lived” spaces of competition—the socially and geographically bound spaces of reciprocally oriented interactions between schools and families that operate as “fields” (Woods, Bagley, & Glatter, 1998).…”
Section: Overview Of the Yearbook’s Contributionsmentioning
confidence: 99%
“…The importance of public-private partnership is that it allows for a simultaneous increase in the investment support for higher education (due to joint public and private financing) and an increase in the effectiveness of university management-due to the flexibility of private investors and public control (Termes et al, 2020;Barrera-Osorio et al, 2022). Results obtained in similar studies show that the development of higher education in the social and investment model of economic growth is determined by the quality of vocational training (Olmedo-Moreno et al, 2021;Vanderburg et al, 2022) and ease of finding skilled employees (Halili et al, 2022;Maddah et al, 2023) (quantitative accessibility of skilled employees).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Crosscountry research highlights that there is no evidence that PPP schools perform better than public schools, and a study of 17 countries found that in the majority of countries, PPP schools were reinforcing social disparities by disproportionately serving students in upper income quintiles (Baum 2018). Educational PPPs in the Philippines turned out to be unaffordable for poor families and to accentuate school segregation and stratification (Termes et al 2020). Meanwhile, students in PPP schools in Uganda were found to perform poorly on assessments compared to their counterparts in government schools and other private schools (ISER 2016).…”
Section: The World Bank In Education-key Lessons To Be Learnedmentioning
confidence: 99%